2011
DOI: 10.1002/jssc.201100479
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of tauro‐ and glyco‐conjugated bile salts with α‐cyclodextrin and hydroxypropyl‐α‐cyclodextrin studied by affinity capillary electrophoresis and molecular modelling

Abstract: The interaction of the bile salts taurocholate, taurodeoxycholate, taurochenodeoxycholate, glycocholate, glycodeoxycholate, and glycochenodeoxycholate present in man, dog, and rat with α-cyclodextrin and 2-hydroxypropyl-α-cyclodextrin was investigated by mobility shift affinity capillary electrophoresis. The cyclodextrins are applied as excipients for solubilisation of drug substances with poor aqueous solubility. Accurate determination of stability constants is challenging for weak analyte-ligand interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…For example, α-CD has a high affinity for fatty acids, flavor molecules and other hydrophobic molecules [ 2 4 ]. However, α-CD has a low affinity for the steroid structure because the cavity size of α-CD is smaller than the structure [ 3 , 5 ]. α-CD has various effects on stabilization of fatty acids, flavor retention and emulsion formation of triglycerides via the formation of an inclusion complex [ 4 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, α-CD has a high affinity for fatty acids, flavor molecules and other hydrophobic molecules [ 2 4 ]. However, α-CD has a low affinity for the steroid structure because the cavity size of α-CD is smaller than the structure [ 3 , 5 ]. α-CD has various effects on stabilization of fatty acids, flavor retention and emulsion formation of triglycerides via the formation of an inclusion complex [ 4 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A target temperature of 25°C was selected to allow for comparison with previous investigations, even though this is not the physiologically relevant temperature, where mobility‐shift ACE was found to be an efficient method for investigation of the interaction between glyco‐ and tauro‐conjugated bile salts and neutral CDs . However, the highly charged nature of SBEβCD makes it analytically more challenging as compared to its neutral counter parts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both bile salts and phospholipids can act as guest molecules in CD complexes. [216][217][218] As mentioned earlier in this review, in multicomponent systems, competition between different guest molecules may result in reorganization of complexes and in dynamic systems, such as the intestinal environment, complex composition (and, consequently, CD aggregation) can change over time. As a result, the aggregation behavior and overall performance of the formulation in biorelevant media and in pure water may strongly differ.…”
Section: Challenges and Opportunitiesmentioning
confidence: 86%